Panorama of environmental contamination by pesticides in the state of Mato Grosso: risk to urban supply (Research, Society and Development, 2021)
The state of Mato Grosso has the largest share of sales of pesticides in the country, because of the agricultural expansion suffered in recent years. Based on the risk of human exposure to these products through the ingestion of contaminated water, this article aimed to identify, analyze and describe the scientific contributions found in the literature on the contamination of water sources used for urban supply in Mato Grosso, analytical methodologies for the treatment of contamination and the public policies focused on its monitoring. It was found that despite the existence of existing legislation to control water quality, there are flaws in the compliance and monitoring of these active principles, a reason that is associated with the high cost for proper treatment, resulting in various environmental and social disorders.